Nalbuphine: some aspects of the research and applications - Logash, Maxim; Pokotylo, Petro; Zboina, Bożena; Stępień, Renata B. (Medical Studies/Studia Medyczne, 2017)
Nalbuphine hydrochloride is a synthetic, non-scheduled opioid agonist/antagonist analgesic, widely used across different branches of medicine. Despite the fact that nalbuphine has been used in the clinical setting for more than 40 years, there is still a lot of controversy regarding its mechanism of action and side-effects, including the development of the addiction to the drug. Recent data demonstrated the increase of non-medical use of nalbuphine. Moreover, in some countries it was placed in list of psychotropic and addictive substances. The increasing popularity of nalbuphine led us to review and analyse the data regarding both clinical and non-clinical applications of the drug. Furthermore, we performed an extensive analysis regarding available experimental models and approaches used in the research of opioid substances. Despite a set of problems in clinical settings due to the opioid nature of nalbuphine, it belongs to an indispensable group of analgesics for pain control.